2017
DOI: 10.1186/s13018-017-0609-9
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated segmentation of callus by micro-CT compared to biomechanics

Abstract: BackgroundA high percentage of closed femur fractures have slight comminution. Using micro-CT (μCT), multiple fragment segmentation is much more difficult than segmentation of unfractured or osteotomied bone. Manual or semi-automated segmentation has been performed to date. However, such segmentation is extremely laborious, time-consuming and error-prone. Our aim was to therefore apply a fully automated segmentation algorithm to determine μCT parameters and examine their association with biomechanics.MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…Tb.N was significantly increased, while Tb.Th showed an increasing trend in 5e -treated rats compared with the vehicle (Figure C). Increased BV/TV, Tb.Th, and Tb.N at the fracture site indicated greater callus formation through new bone regeneration (woven bone), which would facilitate its transformation into the lamellar bone and improved callus biomechanical property . From the calcein labeling study, we observed that 5e (5 mg/kg) was comparable to PTH (130% increase with 5e vs 184% with PTH) (Figure D,E).…”
Section: Resultsmentioning
confidence: 99%
“…Tb.N was significantly increased, while Tb.Th showed an increasing trend in 5e -treated rats compared with the vehicle (Figure C). Increased BV/TV, Tb.Th, and Tb.N at the fracture site indicated greater callus formation through new bone regeneration (woven bone), which would facilitate its transformation into the lamellar bone and improved callus biomechanical property . From the calcein labeling study, we observed that 5e (5 mg/kg) was comparable to PTH (130% increase with 5e vs 184% with PTH) (Figure D,E).…”
Section: Resultsmentioning
confidence: 99%
“…For some quantitative analysis, manual segmentation was performed as automated segmentation of fractures can be particularly challenging. While there have been efforts to develop programs that enable accurate automated µCT segmentation (32) , to date they remain less accurate than manual approaches. µCT can increase in power when combined with other scanning and analysis modalities.…”
Section: Discussionmentioning
confidence: 99%
“…The process for segmentation of cortical bone and callus was based in part on previously reported methods (Buie et al 2007; Morgan E, Mason Z, Chien K, Pfeiffer A, Barnes G, Einhorn T et al 2009;Bissinger et al 2017). To complete this task, the algorithm required two initial estimates of the segmentation thresholds.…”
Section: Image Segmentationmentioning
confidence: 99%